2015
DOI: 10.1016/j.anireprosci.2014.12.001
|View full text |Cite
|
Sign up to set email alerts
|

α-Linolenic acid supplementation in BioXcell® extender can improve the quality of post-cooling and frozen-thawed bovine sperm

Abstract: The present study was conducted to determine the effects of supplementing α-linolenic acid (ALA) into BioXcell(®) extender on post-cooling, post-thawed bovine spermatozoa and post thawed fatty acid composition. Twenty-four semen samples were collected from three bulls using an electro-ejaculator. Fresh semen samples were evaluated for general motility using computer assisted semen analyzer (CASA) whereas morphology and viability with eosin-nigrosin stain. Semen samples extended into BioXcell(®) were divided in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
29
1
1

Year Published

2016
2016
2022
2022

Publication Types

Select...
7
1
1

Relationship

2
7

Authors

Journals

citations
Cited by 52 publications
(39 citation statements)
references
References 33 publications
1
29
1
1
Order By: Relevance
“…[24]. A total of 500 µl of sperm was blended with TBARs solution and after that boiled in a water bath at 95°C for 1 h till the combination looked pink.…”
Section: Methodsmentioning
confidence: 99%
“…[24]. A total of 500 µl of sperm was blended with TBARs solution and after that boiled in a water bath at 95°C for 1 h till the combination looked pink.…”
Section: Methodsmentioning
confidence: 99%
“…Other process was followed as the company recommended. Peroxidation of lipid was calculated by melondialdehyde (MDA) production using thiobarbituric acid reactive substances (TBARS) according to the method explained by [15,20]. Table 2.…”
Section: Evaluation Of Semenmentioning
confidence: 99%
“…Authors concluded that, the anti-oxidant effect of these fruit juice improved the chilled semen quality (Daramola and Adekunle, 2015). Kaka et al (2015a) found that addition of 5 ng mL −1 of α -Linolenic acid to the Bioxcell® diluent improved the VAP, VSL, VCL, STR and BCF of frozen bull semen. Moreover, they found, in another study, addition of 5 or 10 ng mL −1 of α-Linolenic acid to tris-based egg yolk diluent increased the general sperm motility (Kaka et al, 2015b).…”
Section: Discussionmentioning
confidence: 94%